2021
DOI: 10.7759/cureus.17610
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Invasive Blood Pressure Monitoring and the Potential Pitfalls of Invasively Measured Systolic Blood Pressure

Abstract: Invasive intraarterial blood pressure measurement is currently the gold standard for intraoperative hemodynamic monitoring but accurate systolic blood pressure (SBP) measurement is difficult in everyday clinical practice, mostly because of problems with hyper-resonance or damping within the measurement system, which can lead to erroneous treatment decisions if these phenomena are not recognized. A hyperresonant blood pressure trace significantly overestimates true systolic blood pressure while underestimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…É considerada, atualmente, como a referência na avaliação da pressão arterial invasiva (PAI) (Al-Qatatsheh et al, 2020;Lam et al, 2021;Pour-Ghaz et al, 2019;Saugel et al, 2020), permitindo a avaliação, de forma contínua, da pressão arterial (PA) e da função cardíaca (Pour-Ghaz et al, 2019), através da análise do contorno da onda de pressão (OP) (Al-Qatatsheh et al, 2020;Lam et al, 2021;Saugel et al, 2020), a qual surge pela transformação da informação mecânica do movimento existente no interior do SA em sinais elétricos, após passagem pelo transdutor da LA (Saugel et al, 2020), apresentando um traçado particular, com uma curva em forma de V invertido, a qual é constituída por DOIs componentes principais, o anacrótico, o qual corresponde ao período de sístole, onde ocorre a ejeção do sangue, representado por uma subida, e o dicrótico, o qual corresponde ao período de diástole, representado por uma descida, onde ocorre o encerramento da válvula aórtica, o que origina um evento fisiológico específico, denominado de nó dicrótico, situado sensivelmente na região medial do componente dicrótico (Nguyen & Bora, 2022).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…É considerada, atualmente, como a referência na avaliação da pressão arterial invasiva (PAI) (Al-Qatatsheh et al, 2020;Lam et al, 2021;Pour-Ghaz et al, 2019;Saugel et al, 2020), permitindo a avaliação, de forma contínua, da pressão arterial (PA) e da função cardíaca (Pour-Ghaz et al, 2019), através da análise do contorno da onda de pressão (OP) (Al-Qatatsheh et al, 2020;Lam et al, 2021;Saugel et al, 2020), a qual surge pela transformação da informação mecânica do movimento existente no interior do SA em sinais elétricos, após passagem pelo transdutor da LA (Saugel et al, 2020), apresentando um traçado particular, com uma curva em forma de V invertido, a qual é constituída por DOIs componentes principais, o anacrótico, o qual corresponde ao período de sístole, onde ocorre a ejeção do sangue, representado por uma subida, e o dicrótico, o qual corresponde ao período de diástole, representado por uma descida, onde ocorre o encerramento da válvula aórtica, o que origina um evento fisiológico específico, denominado de nó dicrótico, situado sensivelmente na região medial do componente dicrótico (Nguyen & Bora, 2022).…”
Section: Resultsunclassified
“…As limitações destes tipos de tecnologia coincidem, em grande medida, com as complicações associadas à LA, uma vez que se refere a presença de artefactos, como a hiperressonância e o "damping" (Hendy & Bubenek, 2016;Lam et al, 2021), aneurisma da aorta e arritmias (Hendy & Bubenek, 2016), resultando numa ineficácia evidente na MH, com consequente repercussão na imprecisão dos dados clínicos (Hendy & Bubenek, 2016;Lam et al, 2021). Existem ainda limitações atribuídas aos dispositivos, embora as causas estejam subjacentes ao paciente em si, como obesidade mórbida (Tejedor et al, 2015, citados por Pour-Ghaz et al, 2019, alterações ao nível da RVS, pacientes com baixo DC (Maeda et al, 2018, citados por Pour-Ghaz et al, 2019 ou instabilidade hemodinâmica (Hendy & Bubenek, 2016).…”
Section: Resultsunclassified
“…It was believed to provide immediate and reproducible measurement of BP [ 3 ]. However, evidence showed that a hyper-resonant blood pressure trace, derived from AC, significantly overestimates true systolic blood pressure and underestimates the diastolic pressure [ 17 ]. From this perspective, AC is also prone to be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Arterial catheterization is the gold DOI: 10.1002/admt.202201814 standard for blood pressure waveform monitoring, but it is difficult to use routinely because it is too invasive and can lead to patient discomfort, hematoma formation, catheter embolism, and increased risk of infection. [8,9] Methods for non-invasive blood pressure waveform monitoring include photoplethysmography (PPG), vascular unloading technique, arterial tonometry, and ultrasonic method. [10] Non-invasive blood pressure waveform measurement techniques are safer, faster, and require less expertise than invasive methods.…”
Section: Introductionmentioning
confidence: 99%